Does parental unemployment affect the quality of their children's first job? - Maria Kleverbeck; Michael Kind (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
In this paper the relationship between parental unemployment at time of children's labor market entrance on the quality of their children's first job is analyzed. Using data from the German Socio-Economic Panel (SOEP) for the years 1991-2012 the quality of the first job in terms of wage, permanent position and full-time employment is examined. The results show a negative correlation between fathers' unemployment at the time of children's labor market entrance and their children's first wage, while no significant relation can be found for unemployment or labor market inactivity of mothers.
Keywords: J31; J62; J64; J65; 330; Parental Unemployment; Quality of First Job